EFFECT OF EXERCISE TRAINING OF DIFFERENT INTENSITIES ON ANTI-INFLAMMATORY REACTION IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - J.-S. Kim; Y.-H. Lee; J.-C. Kim; C.-S. Yoon (Termedia Publishing House, 2014)
The study investigated the effect of high- and low-intensity exercise training on inflammatory reaction of blood and skeletal muscle in streptozotocin (STZ)-induced diabetic male Sprague-Dawley rats (243 ± 7 g, 8 weeks). The rats completed treadmill running in either high-intensity exercise (6 weeks of exercise training, acute bouts of exercise) or low-intensity exercise (6 weeks of exercise training). Non-running, sedentary rats served as controls. To induce diabetes mellitus, rats received a peritoneal injection of STZ (50 mg · kg-1). Rats were sacrificed immediately after an acute bout of exercise and 6 weeks of exercise training. Inflammatory factors were analyzed by ELISA and by immune blotting from the soleus and extensor digitorum longus muscles. In the serum, inflammatory cytokines (IL-1β, TNF-α, IL-6, IL-4) and reactive oxygen species (ROS) (nitric oxide and malondialdehyde) increased in diabetic rats. However, all exercise training groups displayed reduced inflammatory cytokines and reactive oxygen species. In skeletal muscles, low-intensity exercise training, but not high intensity exercise, reduced the levels of COX-2, iNOS, and MMP-2, which were otherwise markedly elevated in the presence of STZ. Moreover, the levels of GLUT-4 and MyoD were effectively increased by different exercise intensity and exercise duration. Low-intensity exercise training appeared most effective to reduce diabetes-related inflammation. However, high-intensity training also reduced inflammatory factors in tissue-specific muscles. The data implicate regular exercise in protecting against chronic inflammatory diseases, such as diabetes.